2020
DOI: 10.29252/payesh.19.4.423
|View full text |Cite
|
Sign up to set email alerts
|

Psychometric evaluation of the Medical Science Graduates' Cultural Competency Questionnaire

Abstract: Psychometric evaluation of the Medical Science Graduates' Cultural Competency QuestionnaireZahra naghizadeh moghary 1 , Abbas abbas pour 1 , Saeed ghiasi nodooshan 1 , Mahdi feiz 2 , Jalil kuhpayehzadeh 3

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…Comparing the results of this study with other questionnaires designed to assess cultural competence, we concluded that despite many questionnaires and scales being developed to assess cultural competence, only some had been developed based on a particular model or theory. Moreover, some of these scales include a great number of items that affect the applicability of those scales (Naghizadeh et al., 2020; Yadollahi, Ebadi, & Asadizaker, 2020; Yadollahi, Ebadi, MolaviNejad, et al., 2020). For example, the Cultural Competence Health Practitioner Assessment scale has 67 items, and the Transcultural Self‐Efficacy Tool (TSET) has 83 items (Jeffreys & Smodlaka, 1996; Osmancevic et al., 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Comparing the results of this study with other questionnaires designed to assess cultural competence, we concluded that despite many questionnaires and scales being developed to assess cultural competence, only some had been developed based on a particular model or theory. Moreover, some of these scales include a great number of items that affect the applicability of those scales (Naghizadeh et al., 2020; Yadollahi, Ebadi, & Asadizaker, 2020; Yadollahi, Ebadi, MolaviNejad, et al., 2020). For example, the Cultural Competence Health Practitioner Assessment scale has 67 items, and the Transcultural Self‐Efficacy Tool (TSET) has 83 items (Jeffreys & Smodlaka, 1996; Osmancevic et al., 2020).…”
Section: Discussionmentioning
confidence: 99%